STUDI STILISTIKA AYAT KISAH NABI ADAM Q.S. AL-BAQARAH DAN Q.S. AL-A’RAF - Syahrul Rahman; Jon Pamil (UIN Siber Syekh Nurjati Cirebon, 2023)
This article examines the editorial differences between Adam's story verses, which are spread across two surahs, al-Baqarah and al A'raf. The academic discussion in this study begins with the assumption of some Western scholars who think that the language of the Quran is not systematic, there is no coherence between sentences, and language styles that jump up and down confuse the reader. The negatif stigma built by Western scholars is contrary to the theory of miracles in the Qur'an promoted by commentators. The Muslim scholars (mufassir) had emphasized the importance of the Quran's language as part of its miracles. This article traces the form of editorial similarity in the verses of the Quran contained in the two surahs above and is analyzed using a descriptive analysis approach. The object of this library research is the verses of the stories of Prophet Adam in surah al-Baqarah and al A'raf. The stylistic approach of the Quran is considered capable of testing the validity of the research’s result by Western scholars who negatifly judge the language style of the Quran. The findings of this research confirm the miraculous inimitability of Quranic expressions. It also refutes some Western theories regarding the unsystematic language of the Quran. Artikel ini fokus mengkaji perbedaan redaksi ayat kisah Nabi Adam yang tersebar di dua surah, surah al-Baqarah dan surah al-A’raf. Diskusi akademis pada penelitian ini berawal dari asumsi sebagian sarjana Barat yang beranggapan bahwa bahasa al-Qur’an tidak sistematis, tidak adanya koherensi antar kalimat dan gaya bahasa yang loncat-loncat membuat pembaca bingung. Stigma negatif yang dibangun Sarjana Barat ini bertolak belakang dengan teori kemukjizatan bahasa al-Qur’an yang diusung oleh para sarjana tafsir. Jauh sebelumnya, para ulama tafsir al-Qur’an sudah menyuarakan adanya keistimewaan bahasa al-Qur’an dan ia bahagian dari kemukjizatan al-Quran. Artikel ini melacak bentuk kemiripan redaksi ayat al-Qur’an yang termuat di dua surah di atas dan dianalisa dengan menggunakan pendekatan analisis eksplanatori, yaitu menjelaskan bagaimana tingginya sastra bahasa al-Qur’an dalam ber-ta’bir. Penelitian ini murni penelitian kepustakaan dengan menjadikan ayat kisah Nabi Adam yang tercantum dalam surah al-Baqarah dan surah al-A’raf sebagai objek penelitian. Pendekatan stilistika al-Qur’an dianggap mampu untuk menguji kevalidan hasil penelitian sarjana Barat yang menilai negatif terhadap gaya bahasa al-Quran. Temuan penelitan ini adalah mengkonfirmasi adanya miraculous inimitability of Quranic expressions, keindahan bahasa al-Qur’an tiada tandingan. Sekaligus membantah sebagian teori Barat terkait ketidaksistematikan bahasa al-Qur’an.